Hubungan Antara Bauran Pemasaran dan Kepuasan Konsumen Cau Chocolates Desa Marga, Kabupaten Tabanan - JUNIARI, NI MADE; PARINING, NYOMAN; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
Relationship Between Marketing Mix and Customer Satisfaction of Cau Chocolates in Marga Village, Tabanan Regency This study aims to determine the level of consumer satisfaction seen from the marketing mix indicators and determine the effect of marketing mix indicators on customer satisfaction of Cau Chocolates in Marga Village, Tabanan Regency. This study uses descriptive qualitative and quantitative methods with a total sample of 80 Cau Chocolates consumers determined using the purposive sampling method. The data analysis technique uses Structural Equation Modeling (PLS-SEM). The results showed that the level of customer satisfaction Cau Chocolate produced a score of 3.63 which was included in the category of satisfaction. Meanwhile, the results of analysis using SEM analysis produce, (1) product indicators positively and significantly influence consumer satisfaction, (2) price indicators positively and significantly influence consumer satisfaction, (3) place indicators positively and significantly influence satisfaction consumers, and (4) promotion indicators have a positive and significant effect on customer satisfaction.